PP.32.08: CISTATIN C FOR SCREENING RENAL DISEASE RISK. (June 2015) - Robles, N.; Gallego, R. Hernandez; Chavez, E.; Bayo, M.A.; Gomez, J. Lopez; Cidoncha, A.; Candia, B. Gonzales; Cubero, J.J.
Abstract : Objective: Cistatin C have shown to be a cardiovascular risk marker as well as a renal function parameter with higher sensitivity and specificity than serun creatinine. KDIGO guidelines recommend to measure cistatin C in stage IIIa patients without other signs of renal damage. It have been evaluated the use of cistatin C for detecting renal risk in patients with normal serum creatinine. Design and method: The sample included 738 patients (mean age 58. ± 14.6 years, 457 male) treated in the outpatients office. It was measured cistatin C, serum creatinine, and 24 h microalbuminuria and proteinuria. Glomerular filtration rate (GFR) was calculated using the MDRD4-IDMS and Hoek equations. Two hundred and fifty six subjects were diabetics. It was considered as normal serum creatinine < 1.4 mg/dl for males and < 1.2 mg/dl for females. Results: In all 422 patients showed normal serum creatinine. Of them, 47 using Hoek formula and 64 using MDRD4 equation have a GFR < 60 ml/min; on the other hand, 121 patients had increased levels of cistatin C (69 with GFR > 60 ml/min calculated through MDRD4 equation). Prevalence of microalbuminuria was higher in patients with high cistatin C levels (68.5% vs 40, 1%, p < 0.01). For patients with normal serum creatinine and GFR > 60 ml/min the prevalence of microalbuminuria was 66.7% if cistatin C was elevated and 39.2% when cistatin C was normal (p < 0.01). Conclusions: In a group of patients with normal serum creatinine an increased cistatin C level was found in more than a half of the sample, even when GFR was > 60 ml/min. In this subjects the prevalence of microalbuminuria was increased. Cistatin C seems to be a renal risk marker better than serum creatinine and more sensitive than estimated GFR.